Temporal and spatial variation characteristics of major air pollutants in Shanghai from 2019 to 2022 - Zhai Chaoyi; Duan Lian (E3S Web of Conferences, 2024)
To inlustrate the spatio-temporal distribution and trends of six major air pollutants (PM2.5, PM10, O3, NO2, SO2, and CO), a comprehensive analysis of atmospheric pollution data in Shanghai from 2019 to 2022 was conducted. The results showed that all the six air pollutant except O3, decreased yearly, with PM2.5 experiencing a roughly 24.3% decrease and NO2 showing a reduction of approximately 35.8% from 2019 to 2022. However, O3 concentrations exhibited a significant increase in 2022, rising by 13.1% compared to 2021. Seasonal variations indicate severe ozone pollution in summer and significant particulate matter pollution in autumn and winter. Spatial distribution characteristics highlight higher PM2.5 concentrations in the western regions of Shanghai compared to the eastern regions, possibly linked to predominant wind directions and pollutant source distribution. Correlation studies indicate a strong positive correlation between PM2.5 and PM10 in Shanghai’s atmosphere, while a pronounced negative correlation exists between O3 and NO2. In January 2022, prevailing airflow from the northeast, transported atmospheric pollutants and particulate matter southward, adversely elevating concentrations of PM2.5 and other pollutants for that month. In May 2022, airflow from both the east and southwest likely transported O3 and its precursors from diverse sources to Shanghai, aiding in explaining the elevated O3 concentration during that month.